RICE PROCUREMENT OPTIMIZATION USING DYNAMIC PROGRAMMING - MAIDIANA PUTRI , CHIKA
Abtract : Rice procurement problem which is executed by B institution will be discussed in this nal project. Each month, B institution has responsibility to procure the rice in a certain amount. It has seven working areas that each of them must do procurement per month. The problem occurs when not all working areas have the ability to procure the rice according to the specied target. For this case B institution must have a desicion to provide rice procurement by donating from surplus working area to desit working area based on the most minimum cost. This problem can be classied as dynamic programming and here it will be solved using Dijkstra algorithm. This nal project will present two models which related to problems faced by B institution. First model is one working area model, and the second is two working area model. The second model is made by showing interaction of some working areas to make rice procurement with minimum cost which is they can act as donor if it is surplus, and as recipient if it is desit.